Pengaruh Sosialisasi SAK-EP, Tingkat Pendidikan Pemilik, dan Pemahaman Akuntansi Terhadap Implementasi SAK-EP Pada UMKM Di Kota Palembang - Fernanda; Nafsiah, Siti Nurhayati (JURNAL ILMIAH EDUNOMIKA, 2025)
The Financial Accounting Standards for Entities Without Public Accountability (SAK EP) were introduced to help micro, small, and medium enterprises (MSMEs) prepare financial statements that are simple yet in line with accounting standards. However, their implementation remains relatively low in practice. This study aims to examine the influence of socialization activities, owners’ educational background, and accounting knowledge on the implementation of SAK EP among MSMEs in Palembang City. A quantitative approach was applied using multiple linear regression analysis, with data collected through questionnaires distributed to MSME owners. The findings reveal that both the educational level of business owners and their accounting understanding significantly affect the adoption of SAK EP, whereas socialization does not have a significant impact. These results support the Theory of Planned Behavior, emphasizing that perceived behavioral control plays a crucial role in shaping accounting practices. The implication is that improving accounting literacy and providing technical training are more effective strategies than relying solely on administrative socialization to enhance the application of SAK EP. Keywords : SAK EP, MSMEs, education, accounting understanding, socialization